International Migration Management and Sustainable Development: Challenges Against the Background of Increasing Globalization, Changes in Commerce, COVID-19, and War - Kotlyarevskyy, Yaroslav; Voloshchuk, Kateryna; Bosak, Andriy; Berest, Ihor; Shliakhetko, Vitaliy; Karaim, Myroslava (Journal of Ecohumanism, 2024)
According to established and formalized ideas, the goals of sustainable development are considered to the greatest extent due to the reduction of man-made pressure on the environment in order to provide the next generations with the opportunity to exist in favorable natural conditions. The issue of the impact of migration on the process of achieving the goals of sustainable development is considered indirectly, but has a tendency to deepen due to the quantitative growth of the group of migrants, which already affects the balance of environmental and socio-economic development of increasingly larger territories. The problem is aggravated by the reasons for the growth of migration flows and the significance of the impact on the labor market of the exporting country and the importing country. Today, using the example of Ukraine, which, being the leader among the countries exporting labor, is experiencing a difficult stage of military confrontation with the Russian Federation, one can actually outline a deeper problematic of the connection, since most EU countries were forced to be involved in this process. Ukraine and the EU countries, while caring about achieving sustainable development goals, differ in their policies towards migrants under different influences of key factors (before and during COVID-19 and in conditions of high intensity of military actions), which allows us to form a holistic vision of the problem, which should be addressed at the international level by consolidating the efforts of all participants..